– Legal protection for planning designs of integrated circuits – comparative study - Ali, Wael Mohamed Refaat Ibrahim (Journal of Economic, Administrative and Legal Sciences, 2018)
The integrated circuits are one of the pillars of the technology industry in the world. They are indispensable in the various equipment, machinery and equipment. Each unit consists of one integrated circuit or more. With the availability of the design components of the integrated circuits, the owner is entitled to obtain a protection document known as a design certificate for the integrated circuits by the competent authority to grant this certificate in the grantor country, and we will discuss in this research the concept of design certificate for the integrated circuits, indicating their economic importance, Protection and registration of the schematic design of integrated circuits, and then review the legal effects of granting such protection to the design of the integrated circuits and the rights and obligations of the design owner with the statement of exceptions prescribed in this regard, and review the course of Egyptians legislators and Saudi Both of them in Giving protection, Using the descriptive analytical approach based on opinions and judgments on the rules on the protection of design designs of integrated circuits, and using the comparative method in relation to the national legislations under study represented in the Egyptian Intellectual Property Protection Law No. 82 of 2002 and its executive regulations, the patent system and design designs for integrated circuits, plant varieties and models Which was issued by Royal Decree No. M / 27 dated 29/5/1425 H, approved July 17, 2004 and its executive regulations. The research revealed the adequacy of the rules governing the protection of planning designs to the integrated circuits, whether in Egyptian legislation or in the Saudi system, as well as the agreement of these rules with the provisions of the relevant international conventions and treaties such as the Paris Convention, the TRIPS Agreement and the Washington Convention for Integrated Circuit Planning Designs. The research included several recommendations, the designations are appropriate for their nature and the legislations in question are not sufficiently satisfied with the rules governing the patent. There is a substantial difference between them, which was discussed in detail through the research, as well as the need to review the fees imposed as a condition for providing legal protection. In support of the technology industry in our Arab world as one of the emerging markets in this field.